Consequences and Influences of the Economic Crisis on the Efficiency of Romanian Enterprises (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
This paper aims at investigating the effects of the economic and financial crisis (whose effects have been felt in Romania since the end of 2008) on the efficiency of companies in our country. Romanian companies are analyzed by means of efficiency indicators such as labor productivity, average number of employees, turnover structure and added value etc. Additionally, this research paper aims at assessing the impact of the crisis on the behavior of managers in our country in uncertain crisis environment by monitoring turnover correlations - value added, value added - profit tax - investment. The study is exclusively focused on the secondary and tertiary sector of the Romanian economy: industry, constructions, trade and services, both from a cumulative (overall), and a section perspective. The analysis also aims at correlating development in the economic sectors mentioned above, the evolution of the Romanian economy in terms of economic and financial crisis.